TINJAUAN YURIDIS PENERAPAN CUKAI MINUMAN MANIS DALAM PERSPEKTIF FUNGSI HUKUM - Abid, Muhammad Azzamul; Hadi, Fikri; Gandryani, Farina (Jurnal Yustisiabel, 2025)
The issue of health among the younger generation is currently a significant concern in Indonesia. One of the key issues lies in the consumption of unhealthy products, such as sugary drinks. This consumption has led to an alarming rise in the number of people diagnosed with diabetes among the younger population. It is imperative for the government to utilise legal instruments to tackle this challenge, one such instrument being the imposition of an excise tax on sweetened beverages. This article will examine the implementation of excise tax on sweetened flavoured drinks in terms of legal function theory. This research is a legal research with a conceptual and statute approach. The results revealed that the implementation of an excise tax on sweetened flavoured drinks can be associated with one of the functions of law as postulated by Roscoe Pound, namely as a means of social control, thereby enabling individuals to adopt a healthier lifestyle by reducing their consumption of sugary drinks. This legal function can be directed towards the means of development and renewal, as argued by Mochtar Kusumaatmadja. This may be achieved through the imposition of excise tax on sweetened beverages, with the aim of fostering a healthy young generation in Indonesia. Thus, the government is able to protect the community, as well as making progress towards the realisation of the Golden Indonesia generation 2045.